Kazakh petroglyphs as a base for the creativity of designers of Kazakhstan - Джамиля Бектиярова; Алима Сабитова; Камиля Абилкаламова; Айсулу Алданаева; Асель Татаева (Проект Байкал)
This article provides information on petroglyphs of the world and the Republic of Kazakhstan. The table on the use of motifs of Kazakh petroglyphs in modern Kazakhstan is given. It is noted that the immense potential of ancient rock art is widely used by modern designers of Kazakhstan. Materials and techniques of work are diverse. The areas of use involve all spheres of human life. At the same time, there is a certain element of randomness in the use of rock art motifs. The public, cultural, and material significance of the popularization of rock art in Kazakhstan was also voiced.